Application of finishes in Pasar Payang / Ahmad Naqiuddin Ahmad Ramzi - Ahmad Ramzi, Ahmad Naqiuddin (2021)
Finishing works is important any types of building as it gives it a finishing touch and adds beauty and comfort the building. It is the final process of any construction the objectives and aim of this report is to study its purpose, methods, and types of finishes available in the case study building which is the Pasar Payang in Kuala Terengganu. The methods used to do that is by observation and supervision of workers. This is done while the workers do their jobs. Document reviews and interview the supervisors and subcontractors are also the method in completion of the aim of this report. The design of study for this topic is to see the finishes applications in the building. There are different types of finishes used in the case study building which helps gain more information about the study. In conclusion, there are many types of finishes used in the building and each type of them has their own purposes and functions to complete the building and make it one of the best frame structure building in the state.